PERILAKU KELUARGA SADAR GIZI DENGAN STATUS GIZI ANAK BADUTA DI KABUPATEN MAMUJU - Andi Salim; Muh Hasyim (Jurnal Kesehatan Manarang, 2016)
Malnutrition problems in Mamuju is still high in 2014. The results of nutritional assement status (PSG) in West Sulawesi on 2014 is underweight 39.7%, very underweight 20.5% and stunting 39.9% from the highest of five districts. The aim of this study is to determine the relationship between the incidence of behavior Kadarzi with undeweight and stunting. Samples of this study are children aged 0 – 24 months with total population with 150 children. Independent variable is Kadarzi behavior of the family, dependent variabel is nutritional status and sub variable is age, gender, body weight and body lenght. Samples were obtained through interviews and direct measurements from children. The method is analitic survey with cross sectional study. Statistical test with T test (Independent T-Test). The result is there was a relation between behavior of kadarzi with underweight and thin, there is no relation between behavior of kadarzi and stunting.